Draft legislative environmental impact statement on all-terrain vehicles for subsistence use in Gates of the Arctic National Park and Preserve, Alaska. - United States. National Park Service. Alaska Regional Office. (Anchorage, Alaska : U.S. Dept. of Interior, National Park Service, Alaska Regional Office, 1991)
"January 1991." Shipping list no.: 91-107-P. Includes bibliographical references (p. 339-344). Mode of access: Internet.